The Role of the Institution of Complaints in the Formation of a New Reality in Russia - Bessonova, Olga (Journal of Economic Sociology, 2023)
The article continues the discussion initiated by D. Litvintsev about the role of the institution of complaints in Russian economic practice, in particular, in housing and communal services. Previously, O. Bessonova’s articles defended the position of the institution of complaints as an important and effective feedback signal that can be traced throughout the historical development of the distribution economy in Russia and the only legal channel for protecting citizens’ rights in the field of service provision at the present time. D. Litvintsev refuted this statement and gave a classification of complaints, on which he based his argument. O. Bessonova’s attempt to show the inconsistency of both the classification of complaints itself and the argumentation built on its basis led D. Litvintsev to strengthen his denial of the importance of the institution of complaints and shift the focus of the discussion to the abuses and dysfunctions of this institution. This article analyzes the opponent’s methodology for constructing a classification of complaints and the vicious logical circle to which it leads. The fact is that the structure of complaints according to D. Litvintsev initially contains subjective and negative evaluations (erroneous complaints, impulsive complaints, denunciations) and on this basis a conclusion is drawn about abuses. At the same time, no statistics, no interviews with management companies, or examples of different types of complaints were given. To move to the semantic level of the discussion, the problematization formulated by E. Bogdanova was used: why administrative complaints were not completely replaced by lawsuits during the construction of the legal system and market economy, but on the contrary, were not only preserved but also expanded the range of their action in modern Russia? The answer to this key question, which forms the essence of this discussion, can only be found within the framework of the theory of distribution economy. Based on this theory, a forecast is made about the role of civil complaints in the transformation of the institutional system of Russia.